La integración regional, ámbito emergente de políticas de desarrollo en Centroamérica - Caldentey del Pozo, Pedro (Revista Española de Desarrollo y Cooperación, 2023)
The Central American Integration System has gained significance in recent years as a field of policy consensus among Central American countries, of policies formulation and as an object of international cooperation. After the crisis of Honduras in the period 2009-2011, the International Conference in support of the Central American Security Strategy and the Action Plan for the revival of the Central American Integration are key elements on which to build a new stage in the process.